Liver Function Tests in Patients of Pre- eclampsia in Bhilai: A Clinical Study - Lodhi, Rashid Ahsan; Roy, Navanil (Indian journal of clinical biochemistry, 2022)
Pre-eclampsia is a multisystem disorder, which occurs only in pregnant women during the second and third trimesters of pregnancy and is associated with raised blood pressure and proteinuria. Liver function Test (LFT) abnormalities occur in 3% of the pregnancies and probably the lesion that causes elevated serum liver enzymes. This study was conducted to compare the liver function tests in pre-eclampsia with normal pregnancy. This study was carried out on 100 pregnant women after 20 weeks of gestation admitted in Obstetrics & Gynaecology units of Shri Shankaracharya Institute of Medical Sciences, Bhilai, and Chhattisgarh. The subjects were divided into two groups. Group A consisted of 50 cases of pre-eclampsia having blood pressure [greater than or equal to] 140/90 mm Hg, proteinuria in 24 h [greater than or equal to] 300 mg and edema. Group B had 50 normal pregnant women after 20 weeks of gestation. The data including BMI, parity, period of gestation, blood pressure and presenting complaints of all subjects were recorded. Serum bilirubin and plasma levels of liver enzymes ALT, AST and ALP were measured. The mean BMI of the cases was increased and that of controls was normal. The mean value of serum bilirubin in cases was increased and in controls it was normal. The mean value of enzymes ALT in cases was increased while in the controls it was normal. Mean serum AST in the cases was increased and in the controls it was normal. Mean ALP level of cases before delivery was increased and in controls it was normal. Increased concentrations of serum bilirubin and liver enzymes ALT, AST and ALP were found in pre-eclampsia cases.